2020
DOI: 10.1038/s41598-020-75808-w
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical property enhancement of chiral Eu(III) complex upon association with DNA-CTMA

Abstract: DNA-based materials have attracted much attention due to their unique photo-functional properties and potential applications in various fields such as luminescent and biological systems, nanodevices, etc. In this study, the photophysical properties of a chiral Eu(III) complex, namely (Eu(D-facam)3), within DNA films were extensively investigated. The enhancement of photoluminescence (more than 25-folds increase of luminescence quantum yield) and degree of circularly polarization in luminescence (glum = − 0.6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…39,41,61,76 These reports highlight the possibility of using CD spectroscopy both to follow the process, usually showing a decrease of the Cotton effect for the Z isomer 38,58,76 to assign the binding mode of both photoisomers, if they are used as ligands, by the pattern of the ICD signal. 38,39 Furthermore, we and others have reported that the chiral environment provided by DNA can influence the chiroptical properties of organic chromophores [77][78][79][80] as well as the stereochemical outcome of a photoisomerization reaction as shown, for instance, for DNA-binding diarylethenes. 29 The same experiment, however, cannot easily be repeated for azobenzenes, as the E isomer is achiral and the Z(P) and Z(M) enantiomers (interconverting helical conformers, Figure 8A) undergo fast isomerization (racemization) in solution 81 i.e.…”
Section: Compound λππ*(E)mentioning
confidence: 91%
“…39,41,61,76 These reports highlight the possibility of using CD spectroscopy both to follow the process, usually showing a decrease of the Cotton effect for the Z isomer 38,58,76 to assign the binding mode of both photoisomers, if they are used as ligands, by the pattern of the ICD signal. 38,39 Furthermore, we and others have reported that the chiral environment provided by DNA can influence the chiroptical properties of organic chromophores [77][78][79][80] as well as the stereochemical outcome of a photoisomerization reaction as shown, for instance, for DNA-binding diarylethenes. 29 The same experiment, however, cannot easily be repeated for azobenzenes, as the E isomer is achiral and the Z(P) and Z(M) enantiomers (interconverting helical conformers, Figure 8A) undergo fast isomerization (racemization) in solution 81 i.e.…”
Section: Compound λππ*(E)mentioning
confidence: 91%
“…The experimental analytical data of (C,H,N) were in good agreement with the theoretical assigning the proposed chemical structures of oxime ligand and it's metal complexes. [10,12]. The thermal decomposition of all complexes are lie at around (278-290) o C temperature and are greater than the free ligands which mainly show good indication for the formation of covalent character among bi dentate 1,10phenanthroline and oxime ligands with cobalt(II), nickel(II) and copper(II) ions…”
Section: Chemistry and Characterizationmentioning
confidence: 99%
“…The antimicrobial activity of the synthesized compounds was evaluated in form of minimum inhibitory concentration (MIC) against the tested microbes via micro-broth dilution method following the procedure stipulated by Clinical Laboratory Standard Institute [10,11]. The microorganisms in this study are Staphylococcus aureus, Streptococcus pneumonia, E. Coli, Salmonella typhi, klebsiella pneumonia.…”
Section: Antimicrobial Activity Studymentioning
confidence: 99%
See 2 more Smart Citations